Anti-Bullying and Sexual Harassment Prevention Socialization to SD Negeri 19 Lakudo Students’ - Samritin, Samritin; Suarti, Suarti; Manan, Manan; Irwan, Irwan; Akbar, Azaz; Saputri, Rezki Eka; Adi, Yudi Prasetya; Sarli, Sarli (Room of Civil Society Development, 2025)
Bullying and sexual harassment among elementary school children remain significant issues that require collective attention, including from academic institutions through community service activities. This article describes the results of an anti-bullying and sexual harassment prevention socialization program conducted for the students of SD Negeri 19 Lakudo, Central Buton Regency, Southeast Sulawesi. The socialization was carried out using a PowerPoint presentation method, followed by an interactive question-and-answer session. The material was delivered in simple language and visualizations appropriate for the developmental stage of elementary school students. The objective of the activity was to enhance students' understanding of bullying and sexual harassment, as well as equip them with basic skills to respond and report such incidents. The results show that the use of visual aids and interactive Q&A sessions successfully encouraged students to ask questions and share personal experiences more openly. This activity has made a meaningful contribution to building a school culture that is safer, child-friendly, and free from violence. Moving forward, integrating anti-bullying and anti-sexual harassment education more systematically into the curriculum could further strengthen these efforts and ensure a sustainable impact.